2017
DOI: 10.1111/jne.12528
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ageing, fasting and high‐fat diet on central and peripheral glucose tolerance and glucose‐sensing neural networks in the arcuate nucleus

Abstract: Obesity and ageing are risk factors for diabetes. In the present study, we investigated the effects of ageing, obesity and fasting on central and peripheral glucose tolerance and on glucose-sensing neuronal function in the arcuate nucleus of rats, with a view to providing insight into the central mechanisms regulating glucose homeostasis and how they change or are subject to dysfunction with ageing and obesity. We show that, following a glucose load, central glucose tolerance at the level of the cerebrospinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
(212 reference statements)
0
3
1
Order By: Relevance
“…These data do contradict previous studies that showed no alterations in hippocampus metabolic profiles, particularly in genetically modified obese rats [73]. Male Wistar-Han rats fed a 40% HFD for 20 weeks demonstrated reductions in glucose tolerance in both plasma and cerebrospinal fluid following glucose challenge, suggesting that HFD induced changes in both central and peripheral glucose tolerance [68] (Table 4).…”
Section: Braincontrasting
confidence: 92%
“…These data do contradict previous studies that showed no alterations in hippocampus metabolic profiles, particularly in genetically modified obese rats [73]. Male Wistar-Han rats fed a 40% HFD for 20 weeks demonstrated reductions in glucose tolerance in both plasma and cerebrospinal fluid following glucose challenge, suggesting that HFD induced changes in both central and peripheral glucose tolerance [68] (Table 4).…”
Section: Braincontrasting
confidence: 92%
“…To show impaired glucose-sensing in AgRP neurons, we recorded neuronal responses to an increase in extracellular glucose from a basal level of 2 mM to 5 mM. These glucose concentrations were chosen to represent brain glucose concentrations under fasting and fed conditions, based on estimates in the CSF from fasted and fed rats and mice ( van den Top et al, 2017 ). Glucose-excited neurons were defined based upon a response characterised by membrane potential depolarisation and/or an increase in action potential firing frequency with increased extracellular glucose ( Figure 1—figure supplement 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Another established outcome of DIO is dysregulation of glucose homeostasis [ 70 , 71 ]. We first examined changes in fasting glucose levels over the treatment period.…”
Section: Resultsmentioning
confidence: 99%